An Enabling Innovation Ecosystem to Accelerate Agriculture Breakthroughs - Merrey, Douglas J.; Loboguerrero Rodriguez, Ana María; Zeppenfeldt, Leanne (Clim-Eat, 2023)
Climate shocks to agriculture are threatening food security, especially in developing countries. Poverty and malnutrition are rising rapidly. Therefore, we must urgently transform our agricultural systems to be productive, sustainable, and equitable, and to contribute fully to lowering greenhouse gas (GHG) emissions. This will require a global “Agricultural Breakthrough”, defined in the Breakthrough Agenda as: “Climate-resilient, sustainable agriculture is the most attractive and widely adopted option for farmers everywhere by 2030.” How can we achieve this? The diversity of the agricultural sector demands multiple “game-changing” innovations to escape the business-as-usual path and rapidly deliver outcomes that reach a positive tipping point. Synergistic interactions among multiple game-changing innovations in hundreds of national and local agricultural systems will cumulatively transform global agriculture. The current agricultural innovation ecosystem is no longer fit for purpose: it is not effective in identifying and promoting game-changing innovations. Reforming the agricultural innovation ecosystem is therefore critical. We use a conceptual framework to analyse five innovation cases to generate lessons learned.